2013
DOI: 10.1155/2013/201681
|View full text |Cite
|
Sign up to set email alerts
|

Parameters That May Be Used for Predicting Failure during Endoscopic Retrograde Cholangiopancreatography

Abstract: Aim. Endoscopic retrograde cholangiopancreatography (ERCP) is frequently used for the diagnosis and treatment of hepatic, biliary tract, and pancreatic disorders. However, failure during cannulation necessitates other interventions. The aim of this study was to establish parameters that can be used to predict failure during ERCP. Methods. A total of 5884 ERCP procedures performed on 5079 patients, between 1991 and 2006, were retrospectively evaluated. Results. Cannulation was possible in 4482 (88.2%) patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
22
0
2
Order By: Relevance
“…We found age was a risk factor for cannulation failure. This result was similar to a finding reported by Emre et al [11] They found the failure rate of cannulation had increased by 1.01-fold for each one-year increase in the patient's age. Lobo et al [12] found that cannulation success rates decreased significantly due to PAD as age increased.…”
Section: Discussionsupporting
confidence: 92%
“…We found age was a risk factor for cannulation failure. This result was similar to a finding reported by Emre et al [11] They found the failure rate of cannulation had increased by 1.01-fold for each one-year increase in the patient's age. Lobo et al [12] found that cannulation success rates decreased significantly due to PAD as age increased.…”
Section: Discussionsupporting
confidence: 92%
“…This is of interest as, according to Balik et al, for each 1-year increase in age the cannulation failure rate appeared to increase by 1.01 (95 %CI 1.004 -1.016, P = 0.002). This analysis, on 5079 patients undergoing ERCP (660 with PAD), investigating parameters that might predict failure, further revealed that PAD did not influence the success rate of cannulation during ERCP [153]. These findings are in accordance with the only other identified full-text available study that takes PAD into consideration as a risk factor for failed cannulation [154].…”
Section: What Is the Impact Of A Pad On The Technical Success And Comsupporting
confidence: 72%
“…We found age was a risk factor for cannulation failure. This result was similar to a nding reported by Emre et al [11] . They found the failure rate of cannulation had increased by 1.01-fold for each one-year increase in the patient's age.…”
Section: Discussionsupporting
confidence: 93%